Between the «Hudson» and the «Potomac»: The Anti-Franco Exile and the Pro-American Policy of the Basque Government in Exile (1936-1979) (Comillas Journal of International Relations, 2019)
This article analyzes the (para) diplomatic policy of the Basque Government in exile in the United States between 1936 and 1979 and its relations with the anti-Franco exile in the search of a common goal: the recovery of democracy in Spain. In its relations with the United States, the Basque Government tried to get the support of the anti-Franco exile.For this purpose, the Basque think tank promoted the Atlanticist strategy, which focused on using as a negotiating weapon the maintenance of the unity of the democratic opposition to the regime before US diplomats. Thus, the elaboration and deployment of this strategy is analyzed along different phases, paying special attention to the existing synergies and objections to this policy. Finally, its evolution is studied taking into account both the different agents and instruments of the Basque Government as well as the political relations and conversations that these maintained with the rest of the organizations of the democratic opposition to the regime.
Keywords: anti-Franco; United States; basque Government; exile; paradiplomacy